Impact of grandchildren on episodic memory and future-time perspective of older adults. - Bruno, Laetitia; Bonin, Patrick; Thiebaut, Gaëtan; Bugaïska, Aurélia (Memory & Cognition, 2026)
This study was designed to investigate the effects of aging in episodic memory and future-time perspective. More specifically, we investigated the impact of grandchildren at encoding on future-time perspective and free recall in older adults. We asked younger and older adults to imagine being stranded in the grasslands of a foreign land without any basic survival items, and to consider either their personal survival or (older adults only) that of their grandchildren. Among the older adults, compared with a pleasantness (control) condition, a survival processing advantage was observed in the grandchild-survival condition, which differed reliably from the personal-survival condition. Furthermore, encouraging the older participants to think about their grandchildren eliminated the differences between older and younger adults on future-time perspective. Having grandchildren seems to serve an adaptive function in old age. Their presence enhances memory performance and seems to enable older adults to cope with their limited life perspective. In line with motivational theories of aging, these results provide valuable insights, opening up new perspectives on the prioritization of goals by older adults and the underlying reasons, including emotional meaning and adaptive purpose.